Manajemen Pembelajaran E-Learning Berbasis Web di SMP Negeri 2 Sidikalang - Rosalima Simanjuntak (UMSU, 2023)
ne important component in improving the quality of education is learning. Learning is a process of interaction between educators or teachers with students and learning resources in a learning environment. Optimizing the use of media in E-Learning based learning can be done by using existing media to be associated with the learning to be taught. Therefore, with E-Learning based learning, it is hoped that it can improve the quality of learning and student learning outcomes at the school to increase . The purpose of this study was to determine learning management, the quality of learning products and the quality of student learning using Web-based E-Learning at SMP Negeri 2 Sidikalang. This type of research uses qualitative research. Data collection techniques using observation, interviews and documentation. The data analysis technique uses data reduction, data presentation, and draws conclusions. And the data validation technique extends participation, increases the persistence of observation, triangulation and consultation with supervisors. The results of the study concluded that SMP Negeri 2 Sidikalanag had implemented Web-based E-Learning Management